162 IMPACT OF FLOW SPEED OF ICG FLUORESCENCE IN THE GASTRIC CONDUIT AND THORACIC INLET SPACE ON ANASTOMOTIC LEAKAGE AFTER ESOPHAGECTOMY. (14th September 2020) - Koyanagi, K; Ozawa, S; Ninomiya, Y; Yatabe, K; Higuchi, T; Yamamoto, M
Abstract:  : We have previously demonstrated that the flow speed of indocyanine green (ICG) fluorescence in the gastric conduit wall could predict anastomotic leakage after esophagectomy. Surround organs via retrosternal route is considered to affect the blood flow in the gastric conduit and anastomotic leakage. In the study, we investigated the impact of the flow speed of ICG fluorescence in the gastric conduit wall and thoracic inlet space on anastomotic leakage after esophagectomy. Methods: A total of 142 patients, who underwent esophagectomy with three-field lymph node dissection, simultaneous reconstruction using a gastric conduit, and cervical anastomosis via retrosternal route, were prospectively investigated. Using ICG fluorescence imaging, blood flow speed of the gastric conduit wall was assessed before and after anastomosis (pre speed and post speed (cm/s)) and correlated with clinicopathological findings. Parameters of thoracic inlet space was assessed using CT scan and correlated with blood flow speed of the gastric conduit wall and anastomotic leakage. Results: Median pre speed was 2.54 (0.73–6.10) cm/s and median post speed was dropped by 1.77 (0.32–8.67) cm/s. Speed reduction (pre speed—post speed) and speed reduction rate ((pre speed—post speed)/pre speed) were negatively correlated with thoracic inlet area (TIA) (P = 0.004, P = 0.021). Pre speed and post speed of the patients with anastomotic leakage were significantly slower than those of the patients without anastomotic leakage, respectively (P < 0.001 and P = 0.050). In 115 patients with pre speed more than 1.98 cm/s, TIA was significantly associated with anastomotic leakage after esophagectomy (P < 0.001). Conclusion: We clearly demonstrated that retrosternal route reduced the blood flow of the gastric conduit wall using ICG fluorescence imaging. Narrow thoracic inlet space might obstruct the blood flow of the gastric conduit wall and cause anastomotic leakage after esophagectomy.